The Changing Face of the Templars: Current Trends in Historiography - Nicholson, Helen J. (History compass, 2010)
Although French, German and British scholars of the nineteenth and early twentieth centuries did much to lay the foundations of scholarly study of the Knights Templars, until the 1970s there were few good general histories of the Templars. Over the last three decades, there has been enormous growth in scholarly research and publication on the history of the Templars, although the mushrooming myths about the order make it difficult for non-experts to distinguish between good and bad history. The Templars were a religious order, protected by the pope. They were also a military order, which fought against Islam in defence of Christian pilgrims and Christian territory and played a key role in the crusades. Their leading members were knights, but most of their members were not warriors, and included priests and women, who served God through prayer rather than by fighting. As well as castles and estates in the Middle East, they had property throughout Europe; they served kings and popes as diplomats and advisors. Far from being secretive - as the mythmakers claim - they opened their churches to local people and lodged travellers in their houses. They were pious men who shared the same faith as the Christians they protected. Historians disagree over where the initiative for the order came from - was it the idea of the first Templars themselves, or did Churchmen suggest it to them? The significance of the Templars’ operations in the ‘crusader kingdoms’ in Palestine and Syria has been much discussed. Historians also disagree over the causes of the trial of the Templars (1307-1312), and how far the Templars were innocent victims of a struggle for supremacy between the papacy and the monarchy of France.